Control of the solid solution decay by heat treatments of deformed niobium-titanium alloys - Chirkina, L.A.; Volchok, O.I.; Lazareva, M.B.; Okovit, V.S.; Storozhilov, G.E. (Functional Materials, 2013)
The features of phase transformation kinetics in solid binary solutions have been studied to show the expediency and efficiency of determining the DMS dependence on the annealing time G(τ) to optimize the heat treatment procedure for superconducting Nb–Ti alloys. The advantages of the G(τ) determination method, compared with a technique usually applied for critical current Jc(τ) measuring, are substantiated. By this method a rapid "in situ" determination of the optimum heat treatment time corresponding to the point of maximum in the G(τ) curve is provided.